Transmission of parasites to people via food: how can we determine their impact and why do we need to know? - Lucy J. Robertson (Food and Waterborne Parasitology)
Foodborne parasites exert a considerable burden on human health, and this can be estimated using the disability-adjusted life year metric, enabling comparisons across regions, age groups, and among parasites and other foodborne hazards. Previous estimates of the burden exerted by different foodborne hazards were published about a decade ago (2015) and an update is planned. These estimates are important, not only for comparative purposes, but also to provide an evidence-based framework for resource allocation for different interventions, including prioritisation of risk management efforts, determining where food safety policy infrastructure should be focused, financing research and innovation, and for targeting supplier and consumer education.Here the potential for improving the previous estimates is discussed, not only by using more recent data, but also by inclusion of foodborne parasitic diseases and disease states that were omitted in the previous estimates. In particular, for example, the inclusion of foodborne infection with Cyclospora cayetensis and with Trypanosoma cruzi are suggested, along with consideration of disease states such as amoebic liver abscess in foodborne amoebiasis. In addition, knowledge gaps, potential interventions, and how intervention effects can be assessed are discussed, using specific examples.